Efficacy of Potential Control Agents Against Rosellinia necatrix and Their Physiological Impact on Avocado - Magagula, Phinda (Plant disease, 2021)
Rosellinia necatrix is the causal agent of white root rot (WRR), a fatal disease affecting many woody plants, including avocado (Persea americana). As with other root diseases, an integrated approach is required to control WRR. No fully effective control methods are available, and no chemical or biological agents against R. necatrix have been registered for use on avocado in South Africa. Fluazinam has shown promising results in the greenhouse and field in other countries, including Spain. The current study aimed to investigate the potential of a fumigant, chloropicrin, and biological control agents (B-Rus, Beta-Bak, Mity-Gro, and Trichoderma) against R. necatrix both in vitro and in vivo as compared with fluazinam. In a greenhouse trial, results showed that Trichoderma and B-Rus were as effective as fluazinam at inhibiting R. necatrix in vitro and suppressed WRR symptoms when applied before inoculation with R. necatrix. In contrast, Mity-Gro and Beta-Bak failed to inhibit the pathogen in vitro and in the greenhouse trial, despite application of the products to plants before R. necatrix infection. Fluazinam suppressed WRR symptoms in plants when applied at the early stages of infection, whereas chloropicrin rendered the pathogen nonviable when used as a preplant treatment. Plants treated with Trichoderma, B-Rus, and fluazinam sustained dry mass production and net CO2 assimilation by maintaining the green leaf tissues despite being infected with the pathogen. This study has important implications for the integrated management of WRR